Water-soluble, heterometallic chalcogenide oligomers as building blocks for functional films. Issue 5 (26th February 2016) - Chane-Ching, J. Y.; Perrin, L.; Puech, P.; Bourdon, V.; Foncrose, V.; Balocchi, A.; Marie, X.; Lavedan, P.
Abstract : Highly water-soluble, discrete, heterometallic, chalcogenide oligomers displaying various valences in a single metal chalcogenide oligomer are proposed for functional films. Abstract : Monometallic chalcogenide aqueous complexes such as (Sn2 S6 ) 4− and (Sn4 S10 ) 4− are widely used as functional ligands with applications in nano-electronics and solar cells. We propose a general process route to the formation of all-inorganic, heterometallic chalcogenide oligomers, thus expanding the range of these functional aqueous ligands. From electrospray ionization mass spectrometry, tetramers were shown to be the most predominant oligomers synthesized in Sn(iv )–Zn(ii )–S(ii ), Sn(iv )–Zn(ii )–Se(ii ) and Sn(iv )–Ga(iii )–S(ii ) systems. While tetramers possessing exclusively one Zn cation were identified in the Sn(iv )–Zn(ii )–S(ii ) system, the full range of solid solutions was achieved for (Sn a –Ga b –S c ) t − oligomers with 1 ≤ a ≤ 4. Using in situ characterization by 119 Sn liquid NMR and Raman spectroscopy, supported by DFT calculations, we demonstrate that the various tetramers adopt a compact adamantane-like structure. The charge of the heterometallic oligomers was shown to be controlled by the doping cation valence and the chalcogenide anion deficiency in the tetramers. These water-soluble heterometallic chalcogenide oligomers can serve as ligands, residue-free dispersants or building blocks for functional film fabrication. Using these oligomers, we report here the fabrication of chalcogenide solar cells employing environmentally friendly, all-aqueous, (Sn a –Zn b –S c ) t − -capped CZTS nanocrystal inks.